Longing for touch and CT-optimal touch perception after interpersonal trauma - Birgit Hasenack; Anouk Keizer (PLoS ONE, 2025)
It has previously been shown that interpersonal trauma (IPT) can negatively impact the experience and perception of social touch. There are, however, also indications that people with IPT might simultaneously experience a stronger longing for touch (LFT). As this has not been systematically investigated, the aim of the current study was to assess the experience of LFT in people with IPT. We additionally assessed if LFT was associated with the perception of CT-optimal touch in this population. In Study 1, 122 women participated in an online experiment. Participants watched and rated videos of CT-optimal (3 cm/s) and CT non-optimal (18 cm/s) touch. They also filled out questionnaires about their LFT and general attitudes towards touch. In Study 2, 44 women participated in a lab-based experiment. Participants were touched by a female researcher with a brush and hand at CT-optimal (3 cm/s) and CT non-optimal (18 cm/s) speeds. They additionally filled out questionnaires about LFT and general attitudes towards touch. In contrast with our hypotheses, women with IPT did not report a stronger LFT or a more negative perception of CT-optimal touch in either study. There was also no significant association between LFT and the perception of touch in women with and without IPT. These non-significant results may be a consequence of the low prevalence of trauma-related psychopathology among participants with IPT in the current study. Implications of these results and suggestions for future research are discussed.